In His Father's Footsteps - Steel, Danielle (New York : Delacorte Press, 2018)
"In His Father's Footsteps is an unforgettable new novel from Danielle Steel, whose countless #1 New York Times bestsellers have made her one of America's favorite storytellers"--
Adult
Keywords: Holocaust survivors. -- Fiction; Families -- Fiction; New York (N.Y.) -- Fiction